Comparative production of cellulases by mutants of penicillium janthinellum NCIM 1171 and its application in hydrolysis of avicel and cellulose - Singhvi, M. S.; Adsul, Mukund G.; Gokhale, D. V. (Bioresource Technology, 2011)
Mutants of Penicillium janthinellum NCIM 1171 were evaluated for cellulase production using both submerged fermentation (SmF) and solid state fermentation (SSF). Mutant EU2D-21 gave highest yields of cellulases in both SmF and SSF. Hydrolysis of Avicel and cellulose were compared using SmF and SSF derived enzyme preparations obtained from EU2D-21. Surprisingly, the use of SSF derived preparation gave less hydrolysis compared to SmF derived enzymes. This may be due to inactivation of beta-glucosidase at 50 degrees C in SSF derived enzyme preparations. SmF derived enzyme preparations contained both thermostable and thermosensitive beta-glucosidases where as SSF derived enzyme preparations contained predominantly thermosensitive beta-glucosidase. This is the first report on less thermostability of SSF derived p-glucosidase which is the main reason for getting less hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: beta-Glucosidase thermostability; Mutant EU2D-21; Solid state fermentation; Submerged fermentation